Estratégias metacognitivas no ensino de ciências para estudantes dos anos iniciais: estimulando o aprender a aprender! - GOMES, Mayara Souza (Universidade Federal do Pará, 2020)
This research describes and analyzes didactic interventions in science teaching, consisting of tasks and strategies specifically designed to awaken and / or exercise metacognitive skills in children of the early years, put into practice in a class of students of the 4th year of elementary school of a riverside school located in the rural area of the northeast region of Pará. It is also proposed a protocol for collecting and analyzing evidence of metacognitive skills in students of basic education. When considering the official documents that indicate the need to learn autonomously, in a contextual way, overcoming mere memorization and in order to contribute to research in the area, the research problem was thought: “What are the possible educational benefits of using certain teaching strategies of metacognitive guidance in classes of students in the early years? ” The analysis and qualitative data of this indicated that this type of activity has an interesting potential to create a favorable environment for students to interact with teachers and colleagues, improve motivation and enthusiasm to learn about the subject and stimulate the acquisition and use of metacognitive skills . Inserted in this dissertation, as a didactic product, examples and guidelines for the use of metacognitive strategies, which can be used in didactic activities in classes of the early years.